Stem Cell Bioprinting: Functional 3D Neural Mini‐Tissues from Printed Gel‐Based Bioink and Human Neural Stem Cells (Adv. Healthcare Mater. 12/2016). Issue 12 (22nd June 2016) - Gu, Qi; Tomaskovic‐Crook, Eva; Lozano, Rodrigo; Chen, Yu; Kapsa, Robert M.; Zhou, Qi; Wallace, Gordon G.; Crook, Jeremy M.
Abstract : On page 1429 G. G. Wallace, J. M. Crook, and co‐workers report the first example of fabricating neural tissue by 3D bioprinting human neural stem cells. A novel polysaccharide based bioink preserves stem cell viability and function within the printed construct, enabling self‐renewal and differentiation to neurons and supporting neuroglia. Neurons are predominantly GABAergic, establish networks, are spontaneously active, and show a bicuculline induced increased calcium response.